(untitled) (Scientific journal of the Fergana State University, 2023)
The article renders the information on the state and processes of copyright protection in Uzbekistan today, in particular, about the role of education in this. The article notes that increasing legal literacy in the field of intellectual property covers not only the general public, but also specialists from relevant state bodies and institutions. It is also emphasized that the formation of the spirit of respect for intellectual property occurs not only with the use of law as an effective tool, but also that this process requires training, information and changes in the supported mechanisms for the formation of the spirit of respect. among the population. Building respect for intellectual property is not only about using the law as an effective tool, but also about training, informing and changing the supported mechanisms for building respect among the population.